Generic cascade analysis technique for setting the minimum targets for resource conservation - Foo, Chwan Yee (2006)
The current drive towards environmental sustainability and the rising costs of raw material and waste treatment have encouraged the process industry to find new ways to reduce resource consumption and waste generation. Concurrently, the development of systematic techniques for resource conservation and recycling within a process plant has seen extensive progress. The advent of process integration technique based on pinch analysis as a tool for the synthesis of optimal resource conservation networks (RCNs) has been one of the most significant advances in the area of pollution prevention over the last decade. However, most of the work on setting targets for resource conservation have been carried out using graphical tools. There is a clear need to develop a numerical technique to quickly and accurately establish the minimum resource targets for a RCN. This thesis presents a new targeting tool called the cascade analysis technique to locate the minimum fresh feed and discharge flowrate targets, pinch location(s) and the resource allocation target for various types of RCNs. The RCNs cases covered in this thesis include continuous and batch water networks, utility gas network as well as property-based network. In the synthesis of water network, water cascade analysis (WCA) is the first numerical technique that is able to handle both mass transfer and non-mass transfer-based water-using processes simultaneously. A new concept to achieve zero discharge via the use of regeneration unit optimisation in water network is also presented. Gas cascade analysis (GCA) and property cascade analysis (PCA) techniques are the first non-iterative numerical targeting tools for the synthesis of utility gas and propertybased networks. The appropriate placement of resource regeneration/purification unit(s) and other process changes options were also assessed using these newly developed cascade analysis techniques.